Worker's Perception Towards Occupational Safety and Health (OSH) Training at Plastic Manufacturing Company in Senai, Johor - Mahshadevi Vijayan,; Ruslan, Rumaizah (Research in Management of Technology and Business, 2021)
Abstract: A high rate of injury and fatality in manufacturing industries occurred due to the insufficiency in Occupational Safety and Health (OSH) training. By that it’s important to investigate type of OSH training implemented and worker’s perception toward the OSH training at workplace based on worker’s safety awareness and supervisor roles. The aim of this study is to measure the correlation between OSH training and worker’s awareness and supervisor roles. A quantitative questionnaire consists of multiple-choice questions and 5-Likert scale from 1 being ‘Strongly Disagree’ to 5 being ‘Strongly Agree’ was distributed among production workers at a plastic manufacturing company in Senai, Johor. The findings indicated the worker’s perception is significantly high towards OSH training based on worker’s safety awareness (M = 3.59, SD = 0.82) and supervisor roles (M = 3.6, SD = 0.9). There is a significant correlation between OSH training and worker’s awareness (r =-0.442, p > 0.01) and supervisor roles (r = -0.376, p < 0.01). The hypothesis 1 and hypothesis 2 were significantly negatively correlated with each other, which giving an insight of future study in OSH training could be explored in wider scopes. Thus, to increase the interest towards OSH training the employer can imply policy on Small and Medium Industry (SMI) Strategic Plan 2020 which associated by DOSH to implement effective OSH practice at the workplace.